Effects of the Social Responsibility for Health program on adolescents' empathic skills, altruistic and health perception - GÜR, KAMER (MARMARA UNIV, FAC MEDICINE, 2018)
Objectives: This study aims to determine the effect of the Social Responsibility for Health (SRFH) program implemented under the leadership of a school nurse on adolescents' empathic skills, altruism and health perception. Materials and Methods: This semi-experimental study used the pre test-post test control group design. It was conducted among 116 adolescents attending a private high school in Istanbul. Fifty-six and 60 of the participants were randomly assigned to the control and experimental groups, respectively. The SRFH program was completed in 14 weeks. The data were collected with the Empathic Tendency Scale, the Scale of Altruism, and the Health Perception. Parametric tests (unpaired t-test and paired t-test) were utilized in the data analysis. Results: While there was no significant difference between the experimental and control groups' total pretest scores of empathic skills and health perception (P>0.05), a significant difference was found between both groups' total posttest scores (P=0.00; P=0.05). Furthermore, the experimental group's total posttest score of altruism and their score averages of social and helpfulness subdimensions increased (P=0.03; P=0.01; P=0.02). Conclusion: The SRFH program implemented under the leadership of a school nurse increased adolescents' empathic skills and health perception and created a difference between the experimental and control groups.
Keywords: Social responsibility; Adolescent; Empathy; Altruism; Health perception